Flatness-based Motion Planning and Model Predictive Control of Industrial Cranes - Khanh, Hoa Bui Thi; Thi, Mai Hoang; Hue, Luu Thi; Nguyen, Tung Lam; Nguyen, Danh Huy (Engineering, Technology & Applied Science Research, 2024)
This study develops a new controller for an industrial crane system in a three-dimensional space. First, the dynamic model of the industrial crane system with two subsystems, the tower crane and the overhead crane is presented. A bidirectional mapping is established between the system's input and output, allowing for efficient trajectory generation. Additionally, the design process explicitly considers the system's kinematic constraints, ensuring safe and feasible motions. This designed trajectory serves as an input for Model Predictive Control (MPC). The MPC is designed with the dual objectives of trajectory tracking and payload anti-swing. Finally, simulations are conducted and the results are compared with those of other control strategies under different cases to demonstrate the effectiveness of the proposed method.